Domestic violence against women: Investigation of the training of health students from institutions in the Municipality of Marabá-PA (Research, Society and Development, 2021)
Domestic violence against women in Brazil needs to be discussed in the health field, from the academic level. This article aimed to investigate the preparation of health students, in the municipality of Marabá-Pará, in the care of women victims of domestic violence. This was a cross-sectional and quantitative study. The data were collected via an applied questionnaire. The documents were prepared on the Google forms platform and sent by messaging application. The questionnaire had 22 objective items, assessing the participants' epidemiological profile and the knowledge acquired on the subject. Among the 49 questionnaires answered, it was noted that the participants were mostly female, were in the 8th semester and were in the age group of 21 years. As for the preparation of care for victims, 69.4% studied the theme in some undergraduate discipline and this contact occurred mainly in Women's Health (44%) and in Nursing in Women's Health care (63.3 %). Regarding the acquisition of psychological preparation to deal with victims during graduation, 63.3% answered that they did not acquire it. As for the notion about legal actions in suspicion of violence against women, 71.4% of the students answered that they know “some, but not all”, and only 16.3% answered that they did. In general, many students do not feel able to provide assistance to victims and point out as the main proposal for improving this situation the inclusion of violence against women in the PPC (Pedagogical Course Project) of health graduations.